1999
DOI: 10.1074/jbc.274.13.9038
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hypoxia-inducible Factor 1 Activation by Carbon Monoxide and Nitric Oxide

Abstract: It has been proposed that cells sense hypoxia by a heme protein, which transmits a signal that activates the heterodimeric transcription factor hypoxia-inducible factor 1 (HIF-1), thereby inducing a number of physiologically relevant genes such as erythropoietin (Epo). We have investigated the mechanism by which two heme-binding ligands, carbon monoxide and nitric oxide, affect oxygen sensing and signaling. Two concentrations of CO (10 and 80%) suppressed the activation of HIF-1 and induction of Epo mRNA by hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
180
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(195 citation statements)
references
References 49 publications
10
180
0
2
Order By: Relevance
“…We cannot exclude, however, that a chemical reaction of NO or one of its metabolites with PHD causes enzyme inactivation at a moiety other than Fe 2ϩ . A number of reports from independent groups suggested that treatment of cells with NO donors under hypoxic conditions inhibited HIF-1␣ accumulation and transactivation of HIF-1 (Liu et al, 1998;Sogawa et al, 1998;Huang et al, 1999). At present we do not have an explanation for the difference between normoxic and hypoxic NO effects.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We cannot exclude, however, that a chemical reaction of NO or one of its metabolites with PHD causes enzyme inactivation at a moiety other than Fe 2ϩ . A number of reports from independent groups suggested that treatment of cells with NO donors under hypoxic conditions inhibited HIF-1␣ accumulation and transactivation of HIF-1 (Liu et al, 1998;Sogawa et al, 1998;Huang et al, 1999). At present we do not have an explanation for the difference between normoxic and hypoxic NO effects.…”
Section: Discussionmentioning
confidence: 55%
“…Regulation of HIF-1 activity by NO is likely to be of (patho)-physiological relevance but molecular mechanisms have not been defined yet. Initial observations suggested that NO inhibits hypoxia-induced HIF-1␣ stabilization and HIF-1 transcriptional activation (Liu et al, 1998;Sogawa et al, 1998;Huang et al, 1999). More recent studies indicated that chemically diverse NO donors or enhanced endogenous NO formation by inducible NO-synthase or NO formation in a coculture system under normoxic conditions provoked HIF-1␣ stabilization, HIF-1 DNA-binding, and activation of downstream target gene expression (Kimura et al, 2001;Sandau et al, 2001aSandau et al, , 2001bZhou et al, 2003).…”
mentioning
confidence: 99%
“…The initial report indicated that NO inhibits stabilization of HIF1 under hypoxia 46 . The underlying mechanism for this effect does not appear to be mediated by nitrosylation of the cysteine residue in the ODD, although deletion of the ODD eliminates the effect of NO in downregulating HIF1α protein levels 47 . As detailed above, under aerobic conditions, NO nitrosylates this residue to prevent degradation of HIF1 (REF.…”
Section: Free Radical Regulation Of Hif1 Under Hypoxic Conditionsmentioning
confidence: 99%
“…NO has been demonstrated to interact with several intracellular signaling cascades, including mitogenactivated protein kinase (MAPK), janus kinase (JAK) and Jun N-terminal kinase (JNK) (Lander, 1997;Kim et al, 1997;So et al, 1998). Additionally, transcription of several gene classes, including cytokines, matrix proteins and hormones, are modulated by NO regulation of nuclear factor κB (NFκB), hypoxia inducible factor 1 (HIF1) and zinc-finger transcription factors (Huang et al, 1999b;Kroncke and Carlberg, 2000;Matthews et al, 1996;Tabuchi et al, 1996;Torres and Forman, 2000). ROS, however, regulates transcription of protein kinases, growth factors and transcription factors, and plays a role in signaling in the vasculature (Burdon, 1996;Giaccia and Kastan, 1998;Maulik, 2002;Meyer et al, 1994;Nose, 2000).…”
Section: Discussionmentioning
confidence: 99%